ONLINE LEARNING MANAGEMENT (IN THE NETWORK) DURING THE COVID-19 PANDEMIC - Fathurrohman, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze online learning management during the Covid-19 pandemic at MA Al-Barokah Probolinggo. This research uses descriptive qualitative research. How to collect data with interviews, observation, and documentation. The subjects of this study consisted of the head of the madrasa, the vice head of the madrasa, teachers and students. The results of the study show that learning management includes planning (planning) by preparing learning tools that are adapted to pandemic conditions, implementing (actuating) learning activities carried out by distance learning (pjj) online, and evaluating (evaluating) to increase learning effectiveness during the covid-19 pandemic. Keywords: Learning Management